Optimal Placement of Leakage Sensors in Urban Gas Networks Based on an Ant Colony Algorithm and System Clustering - Zhewen Sui; Xiaobing Yuan; Baoping Cai; Fangqi Ye; Qingqing Duan; Zhiqiang Zhao; Xiaoyan Shao; Xin Zhou; Zhiming Hu (Applied Sciences)
In urban gas network leakage monitoring, the optimized placement of sensors plays a pivotal role in ensuring public safety and minimizing system maintenance costs. This study introduces an innovative approach that integrates hierarchical clustering with ant colony optimization (ACO) to optimize sensor layouts in urban gas networks. The hierarchical clustering technique is first employed to evaluate the strategic importance of each monitoring node, which subsequently influences the pheromone importance parameter in the ACO algorithm. Furthermore, the proposed method accounts for soil types and gas diffusion characteristics, which affect the pheromone concentration gradient, as well as the physical distances between nodes, which determine the heuristic factors in the algorithm. By finely tuning these parameters, the method achieves a significant reduction in the number of sensors required while ensuring comprehensive network coverage, thereby improving economic and operational efficiency. The optimized sensor layout not only accelerates the response to gas leaks but also enhances the system’s adaptability to complex urban environments. Simulation and field test results validate the effectiveness of this optimization approach, demonstrating its practical value in advancing the safety management of urban gas networks.